Pengaruh Skeptisme Profesional, Independensi dan Pengalaman Audit Investigatif Terhadap Kemampuan Auditor Dalam Mendeteksi Fraud: Studi Empiris Pada Kantor BCA Matraman - Dimas Marsetyadi Putra; Bida Sari; Yan Irianis; Lely Indriati (AKUNTANSI 45, 2026)
This study aims to analyze the influence of professional skepticism, independence, and investigative audit experience on auditors’ ability to detect fraud at Bank Central Asia (BCA), Matraman Branch. This research is motivated by the increasing number of financial statement fraud cases that can reduce audit quality and public trust in the auditing profession. Auditors are required to possess strong capabilities in detecting fraud through the implementation of professional skepticism, a high level of independence, and adequate investigative audit experience. The research method used is associative research with a quantitative approach utilizing SmartPLS 4.0. Data were collected through questionnaires distributed via Google Forms to auditors at BCA Matraman Branch. The population in this study consisted of 45 auditors, with 33 respondents selected as samples using purposive sampling techniques. The results indicate that professional skepticism has a positive and significant effect on auditors’ ability to detect fraud. In addition, auditor independence also has a positive and significant effect on fraud detection ability. Furthermore, investigative audit experience has been proven to positively and significantly influence auditors’ ability to detect fraud. This study is expected to contribute to the development of auditing knowledge, particularly regarding factors influencing auditors’ ability to detect fraud, and to serve as a consideration for companies in improving auditor quality.